MENINGKATKAN PEMAHAMAN TEKS RECOUNT SISWA KELAS X SMA NEGERI 4 PAMEKASAN MELALUI METODE TALKING STICK - Innayah Innayah (Prima Magistra: Jurnal Ilmiah Kependidikan, 2021)
The success of student learning in the classroom is highly dependent on the selection of appropriate learning strategies by the teacher. This study aims to improve the ability of students of class X MIPA-3 SMAN 4 Pamekasan in learning English with recount text material using the talking stick method. This research is a type of classroom action research which consists of two cycles. Each cycle consists of a process of planning, implementing, observing, and reflecting. The research subjects were 36 students. The object of the research is the process and results of learning English in recount text material. Data were collected using observation, documentation, interviews, questionnaires, and tests. The results showed that the students' average score increased from the first cycle of 54.72 to 85.13 in the second cycle. Thus, it can be concluded that the use of the talking stick method has succeeded in increasing students' abilities in recount text material.